2022
DOI: 10.1038/s41522-022-00319-7
|View full text |Cite
|
Sign up to set email alerts
|

Body weight index indicates the responses of the fecal microbiota, metabolome and proteome to beef/chicken-based diet alterations in Chinese volunteers

Abstract: Relationships between meat consumption and gut diseases have been debated for decades, and the gut microbiota plays an important role in this interplay. It was speculated that the gut microbiota and relevant indicators of hosts with different body weight indexes (BMIs) might respond differentially to meat-based diet alterations, since lean and obese hosts have different gut microbiota composition. Forty-five young Chinese volunteers were recruited and assigned to high-, middle- and low-BMI groups. All of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…One reasonable explanation for this result is that modified dietary macronutrients can rapidly shift the composition of gut microbiota in humans and mice, even within a single day. , Conversely, we discovered that some slow-response bacteria were shaped by long-term dietary protein level change but not by modified short-term protein levels. Fecal microbiota has also reported no significant changes during the two-week alteration from beef-based to chicken-based diets . Indeed, long-term dietary intervention is the primary determinant of bacterial taxa, while short-term dietary pattern change influences a small number of gut microbiota. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One reasonable explanation for this result is that modified dietary macronutrients can rapidly shift the composition of gut microbiota in humans and mice, even within a single day. , Conversely, we discovered that some slow-response bacteria were shaped by long-term dietary protein level change but not by modified short-term protein levels. Fecal microbiota has also reported no significant changes during the two-week alteration from beef-based to chicken-based diets . Indeed, long-term dietary intervention is the primary determinant of bacterial taxa, while short-term dietary pattern change influences a small number of gut microbiota. …”
Section: Discussionmentioning
confidence: 99%
“…Fecal microbiota has also reported no significant changes during the two-week alteration from beef-based to chicken-based diets. 40 Indeed, long-term dietary intervention is the primary determinant of bacterial taxa, while short-term dietary pattern change influences a small number of gut microbiota. 41−43 Tryptophan metabolites are potential mediators in diseases such as fatty liver and inflammatory bowel diseases through the kynurenine pathway and direct intestinal microbial metabolism.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The beef, pork, chicken and fish meat proteins displayed beneficial effects on growth and lipid metabolism [20]. In human study, the beef-based to chicken-based diet alterations changed Bacteroides-related proteins and decreased hosts' immunoglobulins in high-and middle-BMI volunteers [21]. Recent studies have also indicated that real meat and plant-based meat analogues have different protein digestion properties in an in vitro digestion model [13].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, differential gut microbial protein expression was detected in stool samples of individuals consuming diets varying in fiber content and glycemic index for 28 days, including those implicated in production and degradation of fatty acids [ 46 ]. Interestingly, replacing beef with a chicken-based diet for two weeks largely affected the abundance of Bacteroides genus, and thus probably induced downregulation of immunoglobulins in feces, especially in high- and middle-BMI Chinese volunteers [ 47 ].…”
Section: Metagenomics Integrating Epigenomics Transcriptomics Proteom...mentioning
confidence: 99%